Russian Practices of Governance in Eurasia: Frontier Power Dynamics, Sixteenth Century to Nineteenth Century, 1st edition - Kendirbai, Gulnar T. (Routledge, 2020)
This book analyses the role of the mobility factor in the spread of Russian rule in Eurasia in the formative period of the rise of the Russian Empire and offers an examination of the interaction of Russian authorities with their nomadic partners.